Potencialidades da aplicação do método timbre para reabilitação de brownfields: uma experiência no município de Santa Gertrudes (SP) - Santos, Carolina Reame [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aims to analyze the feasibility of implementing the method of Tailored Improvement of Brownfield Regeneration in Europe (TIMBRE) project in Santa Gertrudes (SP). The method, created in the European Union during the Seventh Framework Programme for Research and Technological Development, was developed and applied between 2011 and 2014, searching for facilitation and effective actions of rehabilitation on contaminated sites, taking into account the context and experience of various stakeholders. Because it is an innovative methodology on the national scene, official international bibliographies of the project were used as well scientific material already produced on brownfields and environmental management. The work was developed following four main points of research: literature review, analysis and reporting of works already made on site; analysis of the Work Packages; and evaluation of the potential and technical feasibility of the method. As results, it sought to map out a program proposal with a view on rehabilitation, focusing on its positive and negative aspects, and a geographical analysis of the situation

O presente trabalho visa analisar a viabilidade de aplicação do método do projeto Tailored Improvement of Brownfield Regeneration in Europe (TIMBRE) no município de Santa Gertrudes (SP). O método, criado na União Europeia durante o Sétimo Programa para Pesquisa e Desenvolvimento Tecnológico, foi desenvolvido e aplicado durante os anos 2011 e 2014, com o objetivo de subsidiar ações facilitadoras e efetivas de reabilitação de áreas contaminadas, levando em consideração o contexto e a vivência de diversos atores sociais. Por se tratar de método inovador no cenário nacional, foram utilizadas bibliografias internacionais e oficiais do projeto, bem como material científico já produzido sobre brownfields e gestão ambiental. O trabalho foi desenvolvido seguindo 4 principais pontos de pesquisa: levantamento bibliográfico, análise de trabalhos e relatórios já elaborados no local; análise dos Pacotes de Trabalho; e avaliação da potencialidade e viabilidade técnica de aplicação do método. Como resultado, buscou-se traçar propostas de aplicação com vistas à reabilitação, focando em seus aspectos positivos e negativos, e também uma análise geográfica da situação
Keywords: Geografia; Pesquisa bibliografica; Brownfields; Gestão ambiental; Reabilitação; Santa Gertrudes (SP)